Dihydromyricetin Improves High Glucose-Induced Dopaminergic Neuronal Damage by Activating AMPK-Autophagy Signaling Pathway - Li, Qi; Song, Zhenjiang; Peng, Liting; Feng, Shuidong; Zhan, Kebin; Ling, Hongyan (Experimental and Clinical Endocrinology & Diabetes, 2024)
Introduction In recent years, a growing number of clinical and biological studies have shown that patients with type 2 diabetes mellitus (T2DM) are at increased risk of developing Parkinson’s disease (PD). Prolonged exposure to hyperglycemia results in abnormal glucose metabolism, which in turn causes pathological changes similar to PD, leading to selective loss of dopaminergic neurons in the compact part of the substantia nigra. Dihydromyricetin (DHM) is a naturally occurring flavonoid with various biological activities including antioxidant and hepatoprotective properties. In this study, the effect of DHM on high glucose-induced dopaminergic neuronal damage was investigated. Methods The potential modulatory effects of DHM on high glucose-induced dopaminergic neuronal damage and its mechanism were studied. Results DHM ameliorated high glucose-induced dopaminergic neuronal damage and autophagy injury. Inhibition of autophagy by 3-methyladenine abrogated the beneficial effects of DHM on high glucose-induced dopaminergic neuronal damage. In addition, DHM increased levels of p-AMP-activated protein kinase (AMPK) and phosphorylated UNC51-like kinase 1. The AMPK inhibitor compound C eliminated DHM-induced autophagy and subsequently inhibited the ameliorative effects of DHM on high glucose-induced dopaminergic neuronal damage. Discussion DHM ameliorates high glucose-induced dopaminergic neuronal damage by activating the AMPK-autophagy pathway.
Keywords: dihydromyricetin; AMPK; autophagy; dopaminergic neuronal; high glucose